2009 ICSE Workshop on Software Engineering in Health Care 2009
DOI: 10.1109/sehc.2009.5069608
|View full text |Cite
|
Sign up to set email alerts
|

Simulating patient flow through an Emergency Department using process-driven discrete event simulation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…We validated the properties with the gold standard implementation (i.e., in which we had not inserted any defects), and found that the distributions that resulted from applying the properties were not significantly different, with p < 0.05. In the metamorphic testing of JSim, we used the same data set used in the emergency room simulation work presented in [25].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We validated the properties with the gold standard implementation (i.e., in which we had not inserted any defects), and found that the distributions that resulted from applying the properties were not significantly different, with p < 0.05. In the metamorphic testing of JSim, we used the same data set used in the emergency room simulation work presented in [25].…”
Section: Methodsmentioning
confidence: 99%
“…JSim [33] is a rigorous process based Discrete Event Simulation (DEVS) engine that has been effectively used to model and simulate, among other human-centric processes, the flow of patients through a hospital emergency room [25,24]. Developed in Java by researchers at the University of Massachusetts Amherst, JSim's input consists of a complete process definition, represented graphically as a tree of steps and constituent substeps; a set of special resources called agents who perform the steps, such as a nurse in the emergency department; a set of non-agent resources, which include entities that agents may need to carry out the steps, such as beds, x-ray machine, medicine, etc.…”
Section: Jsimmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we have extended JSim [14], an existing discrete-event simulator of Little-JIL/ROMEO processes. Our extensions include support for (1) resource instances, (2) the two-phase resource reservation and allocation, and (3) contention policy constrains to select preferred requests, selection policy constrains to select preferred resources.…”
Section: Jsim Resource-aware Simulatormentioning
confidence: 99%
“…Figure 1 shows the static relations among the entities that define a resource. This metamodel is an extension of an earlier, less expressive resource metamodel [14].…”
Section: Introductionmentioning
confidence: 99%